Nocturnal hypoxia in patients with sleep disorders: exploring its role as a mediator between neurotic personality traits and psychological symptoms - Jiang, Fei; Huang, Jinsong; Fan, Lijun; Dong, Xiaoyan; Yang, Chunyan; Zhou, Wenzhu (Frontiers in Psychiatry, 2024)
IntroductionSleep disorders often coexist with personality and psychological issues, alongside nocturnal hypoxia. This study investigates the potential mediating role of nocturnal hypoxia between personality traits and psychological symptoms in individuals with sleep disorders.MethodsA cohort comprising 171 participants reporting sleep disturbances was recruited from Dalian Seventh People’s Hospital. Psychological symptoms were assessed using the Symptom Checklist-90-R (SCL-90-R), while personality traits were evaluated using the Eysenck Personality Questionnaire (EPQ). Nocturnal hypoxia status was determined through overnight polysomnography.ResultsMediation analysis, conducted using SPSS 23.0, demonstrated that the cumulative time of nocturnal peripheral oxygen saturation (SpO2) < 85% (T85) partially mediated the relationship between neuroticism and various psychological symptoms, including somatization (c=0.207, c’=0.164, a*b=0.043, proportion of mediation 20.8%), interpersonal sensitivity (c=0.360, c’=0.326, a*b=0.034, proportion of mediation 9.6%), depression (c=0.277, c’=0.234, a*b=0.042, proportion of mediation 15.3%), anxiety (c=0.240, c’=0.199, a*b=0.041, proportion of mediation 16.9%), hostility (c=0.241, c’=0.205, a*b=0.036, proportion of mediation 14.9%), phobic anxiety (c=0.271, c’=0.241, a*b=0.030, proportion of mediation 11.1%), and psychoticism (c=0.298, c’=0.266, a*b=0.032, proportion of mediation 10.8%).DiscussionThese findings underscore the potential mediating role of nocturnal hypoxia in the association between neuroticism personality traits and psychological symptoms among individuals with sleep disorders. Our research holds considerable significance in advancing the quest for personalized treatments targeting psychological symptoms in individuals with sleep disorders.